(untitled) (Medical Forum Monthly, 2020)
Objective: To examine the incidence of surgical wound infection in patients undergoing elective and emergency abdominal surgeries. Study Design: Prospective/observational study Place and Duration of Study: This study was conducted at the Department of Surgery, Bacha Khan Medical complex Swabi during from April 2019 to Dec 2019. Materials and Methods: Three hundred and twenty patients of both genders were underwent abdominal surgeries. Patient’s ages were ranging from 5 to 65 years. Patients detailed demographics including age, sex, BMI, type of surgery, comorbidities were recorded after informed consent. Incidence of post-operative wound infection was examined and compare the findings between elective and emergency surgeries. Results: One hundred and ninety (59.38%) were males while 130 (40.62%) were females. 64 (20%) patients were ages <20 years, 160 (50%) were ages 21 to 40 years, 70 (23.75%) were ages 41 to 60 years and 20 (6.25%) had ages above 60 years. 120 (37.5%) patients were underwent elective and 200 (62.5%) underwent emergency surgeries. Overall post-operative wound infection was found in 52 (16.25%) patients while 268 (83.75%) patients had no wound infection. In elective surgeries 8 (6.67%) patients developed wound infection while in emergency 44 (22%) developed wound infection, a significant difference was observed between elective and emergency abdominal surgeries with p-value 0.012. Conclusion: The frequency of wound infection in our settings was high in patients received elective and emergency abdominal surgeries. Moreover, rate of surgical wound infection was high in emergency surgeries as compared to elective.